2006
DOI: 10.1103/physrevlett.97.247802
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Effects in Polymer Crystal Nucleation from the Bulk to Few-Chain Systems

Abstract: We have studied crystallization in poly(ethylene oxide) droplets with volumes ranging over several orders of magnitude. In all samples, homogeneous nucleation is observed, scaling with the volume of the droplet, down to systems with as few as approximately 10 polymer chains. Surprisingly, nucleation is unaffected by the high degree of confinement, despite a large surface-to-volume ratio and the restriction of chains to length scales much smaller than the radius of gyration. Nucleation was also found to be inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 28 publications
6
72
1
Order By: Relevance
“…2.10c). These low Avrami index values around 1.0 suggested that the low-temperature crystallization should be homogeneously nucleated, similar to the results observed for PEO homogeneous nucleation [29,47]. From this crystallization kinetics study, we concluded that the high-temperature crystallization was heterogeneously nucleated in large PVDF droplets, while the low-temperature crystallization was homogeneously nucleated in PVDF nanodroplets.…”
Section: Fractionated Crystallization In Pvdf Nanodropletssupporting
confidence: 83%
“…2.10c). These low Avrami index values around 1.0 suggested that the low-temperature crystallization should be homogeneously nucleated, similar to the results observed for PEO homogeneous nucleation [29,47]. From this crystallization kinetics study, we concluded that the high-temperature crystallization was heterogeneously nucleated in large PVDF droplets, while the low-temperature crystallization was homogeneously nucleated in PVDF nanodroplets.…”
Section: Fractionated Crystallization In Pvdf Nanodropletssupporting
confidence: 83%
“…Later AFM techniques were used for the break-out crystallization as well as the confined crystallization in crystalline-amorphous diblocks. [19][20][21][22] AFM results provide direct information on the crystallization at sampled points, while SAXS and DSC techniques supply average information over the whole systems. In addition, it is necessary for the understanding of crystallization to analyze the crystallization process by using some method developed for homopolymer crystallization.…”
mentioning
confidence: 99%
“…While previous measurements of nano‐confined crystallization in diblocks has typically been carried out with DSC,14, 15, 17, 19, 21 here we use ellipsometry to probe crystallization 10, 36–38. Ellipsometry exploits the fact that linearly polarized light emerges elliptically polarized when reflected from a film covered substrate to obtain the thickness and index of refraction of a film 36.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, there is separation of timescales and the overall crystallization rate is a direct probe of the nucleation rate. Measurements of this type have typically been carried out using small crystallizable droplets that were phase‐separated in an amorphous matrix,1–7 droplets dewetted on some substrate,8–12 or using phase separated block copolymers which provide an ideal system for creating isolated nanoscale domains 13–21…”
Section: Introductionmentioning
confidence: 99%